2017
DOI: 10.4236/tel.2017.76105
|View full text |Cite
|
Sign up to set email alerts
|

Arbitration on Unauthorized Trades by the Trading Member of the Stock Exchange: An Empirical Study

Abstract: This case is an appeal matter with the Stock Exchange on the award passed by the sole arbitrator with regard to a dispute between a client and trading member of the Stock Exchange. Mumbai Capitals Ltd. contended that the award passed by the arbitrator did not take into account of the evidences, supported documents and rules of stock exchange appropriately while determining the case matter and passing the award. Appellant challenged the Award on grounds that the award was beyond the scope of submissions to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These trades were unauthorised because these were not originated from the Respondent i.e., Respondent did not place these orders. It is concluded that the Appli- from the legal discipline but also experts from the securities market with strong domain knowledge of stock market operations [4]. The arbitrators have to consider and review not only the legal provisions and issues but also trading regulations, trading practices, and marketing techniques of the trading members to attract investors to the securities market.…”
Section: Discussionmentioning
confidence: 99%
“…These trades were unauthorised because these were not originated from the Respondent i.e., Respondent did not place these orders. It is concluded that the Appli- from the legal discipline but also experts from the securities market with strong domain knowledge of stock market operations [4]. The arbitrators have to consider and review not only the legal provisions and issues but also trading regulations, trading practices, and marketing techniques of the trading members to attract investors to the securities market.…”
Section: Discussionmentioning
confidence: 99%
“…Investor protection is an important ingredient for the growth and development of the securities markets in any country. The regulatory authorities of the securities markets have to identify and appoint arbitrators in the panel not only from the legal discipline but also experts from the securities market with strong domain knowledge of stock market operations [5]. The arbitrators have to consider and review not only the legal provisions and issues but also trading regulations, trading practices, and marketing techniques of the trading members to attract investors to the securities market.…”
Section: Recommendationsmentioning
confidence: 99%